Land Suitability Evaluation for Sugarcane (Saccharum officinarum L.) Cultivation in the Rejoso Watershed, Pasuruan Regency - Ani Acfiyatul Fardila; Bambang Hermiyanto; Cahyoadi Bowo; Basuki; Subhan Arif Budiman (UNIVERSITY OF LAMPUNG, 2026)
Land suitability evaluation is essential for optimizing crop productivity and promoting sustainable land use. In the Rejoso Watershed, Pasuruan Regency, sugarcane production remains suboptimal due to limited integration of biophysical land characteristics into cultivation management. This study aims to assess land characteristics, classify land suitability, identify limiting factors, and provide land management recommendations for sugarcane cultivation. The analysis considered key variables including temperature, rainfall, drainage, soil texture, effective depth, cation exchange capacity (CEC), base saturation, pH (H₂O), organic carbon, total nitrogen, available phosphorus (P₂O₅), available potassium (K₂O), slope, erosion risk, and flood risk. Land suitability was evaluated using a matching approach based on the Buku Pedoman Penilaian Kesesuaian Lahan Komoditas Strategis Tahun 2016. The results showed that actual land suitability consists of class S3 (Marginally Suitable) covering 22.262 ha (64.3%) and class N (Not Suitable) covering 12.342 ha (35.7%). Potential land suitability includes class S2 (Moderately Suitable) covering 8.562 ha (24.7%), class S3 covering 13.701 ha (39.6%), and class N covering 12.342 ha (35.7%). The main limiting factors identified were temperature, drainage, soil texture, effective depth, nitrogen, phosphorus, base saturation, slope, erosion risk, and flood risk. Recommended management strategies include improving drainage using the Reynoso system, applying dolomitic lime, and SP36 fertilizer. Overall, the Rejoso Watershed demonstrates substantial potential for sugarcane development through improved land management. contributing to national sugar self-sufficiency.